2015
DOI: 10.1152/ajprenal.00163.2015
|View full text |Cite
|
Sign up to set email alerts
|

Deficient acid handling with distal RTA in the NBCe2 knockout mouse

Abstract: In the present study, we report that a mouse model lacking the electrogenic Na ϩ -HCO 3 Ϫ cotransporter [NBCe2/Slc4a5; NBCe2 knockout (KO) mice] developed dRTA after an oral acid challenge. NBCe2 expression was identified in the connecting tubule (CNT) of wild-type mice, and its expression was significantly increased after acid loading. NBCe2 KO mice did not have dRTA when on a standard mouse diet. However, after acid loading, NBCe2 KO mice exhibited complete features of dRTA, characterized by insufficient uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
7
2
Order By: Relevance
“…Because ~20% of patients with dRTA do not have mutations in genes for H + -ATPase or AE1, additional candidate genes have been identified in mouse models of dRTA 3,6. These include HK α 2 (colonic H + –K + -ATPase),75 Kcc4 (K + –Cl − co-transporter, Kcc4),76 genes for the H + -ATPase C, G, and d subunits,77 Foxi1 (the Forkhead transcription factor, Foxi1),78 Rhcg (the ammonia transporter, Rhcg),79,80 Slc26a7 (Cl − –HCO3 − exchanger, Slc26a7, co-localized with AE1),81 DMBT1 (component of the pathway of acidosis-induced conversion of B-ICs into A-ICs, hensin),11 GPR4 (proton sensing G protein-coupled receptor, GPR4),82 NHE4 (Na + –H + exchanger 4, NHE4),83 SLC4A5 (Na + –HCO3 − co-transporter, NBCe2),84 Atp6ap2 (ATPase H + transporting lysosomal accessory protein 2, atp6ap2),85 and Ncoa7 (nuclear receptor coactivator 7, Ncoa7: an H + -ATPase interacting protein), as shown in Table 2 86. Although most of these genes have not been previously identified in human disease, Enerbäck et al identified homozygous FOXI1 mutations in two families with AR dRTA and early-onset SNHL 87.…”
Section: Ar Ae1 Gene (Slc4a1) Mutationsmentioning
confidence: 99%
“…Because ~20% of patients with dRTA do not have mutations in genes for H + -ATPase or AE1, additional candidate genes have been identified in mouse models of dRTA 3,6. These include HK α 2 (colonic H + –K + -ATPase),75 Kcc4 (K + –Cl − co-transporter, Kcc4),76 genes for the H + -ATPase C, G, and d subunits,77 Foxi1 (the Forkhead transcription factor, Foxi1),78 Rhcg (the ammonia transporter, Rhcg),79,80 Slc26a7 (Cl − –HCO3 − exchanger, Slc26a7, co-localized with AE1),81 DMBT1 (component of the pathway of acidosis-induced conversion of B-ICs into A-ICs, hensin),11 GPR4 (proton sensing G protein-coupled receptor, GPR4),82 NHE4 (Na + –H + exchanger 4, NHE4),83 SLC4A5 (Na + –HCO3 − co-transporter, NBCe2),84 Atp6ap2 (ATPase H + transporting lysosomal accessory protein 2, atp6ap2),85 and Ncoa7 (nuclear receptor coactivator 7, Ncoa7: an H + -ATPase interacting protein), as shown in Table 2 86. Although most of these genes have not been previously identified in human disease, Enerbäck et al identified homozygous FOXI1 mutations in two families with AR dRTA and early-onset SNHL 87.…”
Section: Ar Ae1 Gene (Slc4a1) Mutationsmentioning
confidence: 99%
“…In mouse, in situ hybridization studies showed that NBCe2 co-localizes with AQP2, which indicates expression in the principal cells of the CD (Groger et al, 2012). NBCe2 was also detected in micro-isolated connecting tubules (CNT; Wen et al, 2015a), again without reporting how the purity of the samples was tested. Finally, a transcriptome study evaluating renal CD cells revealed that Slc4a5 expression was detected only in a few of the αand β-intercalated cell (2/87 and 1/23, respectively) as well as principal cell (2/74) samples (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several additional mouse models of impaired type A IC H + secretion have been reported which are not yet known to be involved in human disease. These include mice with loss of KCC4 ( Slc12a7 ) (149), slc26a7 (90), Hensin (DMBT1)-CXCL12 complex (150), GPR4 (151,152), NBCe2 (153,154) and ATP6ap2 (155). Species differences also exist in that mice are not necessarily exact phenocopy models of human disease.…”
Section: Introductionmentioning
confidence: 99%